2022
DOI: 10.1111/ejss.13264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different organic amendments on soil pore structure acquired by three‐dimensional investigation

Abstract: The application of organic amendments is an important way to improve soil structure. However, the differences in soil pore properties after adding various organic materials are not fully available, which is important for selecting the most suitable material for soil improvement. In this study, soil pore structures in a field experiment amended with different organic materials (maize straw [MS], cattle manure, mixture of MS and cattle manure, biochar, woody peat, and polyacrylamide [PAM]) were determined by dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…For example, Song et al reported that straw return and intercropping increased the content of water-stabilized aggregates belonging to the 0.5–1.0 mm and 0.25–0.5 mm grain size classes when compared to a single topdressing pattern [ 33 ]. This could be attributed to the accumulation of a rich carbon source substantially increasing the content of soil water-stable aggregates after the decomposition of straw [ 34 ]. Dou et al found that a straw return treatment on three soil types—black soil and brown soil—led to a marked increase in their content of 0.25–2.0 mm and 0.25–1.0 mm water-stable aggregates vis à vis control soils lacking straw, with black and brown soils showing greater improvement in organic carbon content and stabilization of aggregates, resulting in higher crop benefits [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Song et al reported that straw return and intercropping increased the content of water-stabilized aggregates belonging to the 0.5–1.0 mm and 0.25–0.5 mm grain size classes when compared to a single topdressing pattern [ 33 ]. This could be attributed to the accumulation of a rich carbon source substantially increasing the content of soil water-stable aggregates after the decomposition of straw [ 34 ]. Dou et al found that a straw return treatment on three soil types—black soil and brown soil—led to a marked increase in their content of 0.25–2.0 mm and 0.25–1.0 mm water-stable aggregates vis à vis control soils lacking straw, with black and brown soils showing greater improvement in organic carbon content and stabilization of aggregates, resulting in higher crop benefits [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Song et al reported that straw return and intercropping increased the content of water-stabilized aggregates belonging to the 0.5-1.0 mm and 0.25-0.5 mm grain size classes when compared to a single topdressing pattern [33]. This could be attributed to the accumulation of a rich carbon source substantially increasing the content of soil water-stable aggregates after the decomposition of straw [34]. Dou et al found that a The high and low contents of water-stable aggregates in soil are closely related to its resistance to impact and erosion [31].…”
Section: Effects Of Straw Return + Intercropping On the Structure Of ...mentioning
confidence: 99%
“…The application of various organic fertilizers can reduce soil bulk density, improve soil pore structure in the field, improve soil porosity and connectivity, and increase the number of macropores. However, the specific effects of various organic materials are different, and the effect of straw plus organic ferti-https://doi.org/10.17221/64/2023-SWR lizer is the most obvious (Xuan et al 2022). Organic management (application of organic fertilizers while avoiding chemical fertilizers and pesticides) not only increases the total macroporosity in the soil to the optimal range for plant growth but also optimizes the pore size distribution by increasing the relative porosity of the transmission pores (50-500 μm) (Wang et al 2021a).…”
Section: Human Factorsmentioning
confidence: 99%
“…Application of organic amendments is another important way towards improving soil structure. According to a field experiment amended with different organic materials including maize straw, cattle manure, biochar, woody peat and polyacrylamide, Xuan et al (2022) quantified soil pore structure characteristics using a three‐dimensional digital image analysis methodology. They found that application of organic amendments generally reduced bulk density of fluvoaquic soil, and increased the field water capacity as well as the amount of water‐stable macroaggregates.…”
Section: Figurementioning
confidence: 99%